Inkjet printing of transparent InZnSnO conducting electrodes from nano-particle ink for printable organic photovoltaics - Kim, Jihoon; Na, Seok-In; Kim, Han-Ki (ELSEVIER, 2012)
We have demonstrated inkjet-printed indium-zinc-tin-oxide (IZTO) electrodes using IZTO nanoparticle ink for printable organic solar cells (OSCs). By inkjetting of nanosize IZTO particles and rapid thermal annealing (RTA) of the inkjet-printed IZTO films, we were able to obtain directly patterned IZTO transparent conducting electrodes with a sheet resistance of 20.6 Omega/square and an average transmittance of 81.29% without using a conventional photolithography process. Because the inkjet-printed IZTO electrodes were prepared by overlapping the ink-droplets ejected from the nozzle, the mechanism of IZTO nanoink deposition on the surface was investigated. This mechanism defines an optimal ink-droplet pitch to achieve a uniform printing of IZTO lines from the ink-droplets. Despite the low sheet resistance and high transmittance, the OSC fabricated on the inkjet-printed IZTO electrode shows open circuit voltage of 0.45 V. short circuit current of 5.74 mA/cm(2), fill factor of 31.22%, and power conversion efficiency of 0.81% due to porous microstructure of the sintered IZTO nanoparticles. This indicates that the direct patterning of IZTO film by inkjet printing is a promising printable transparent electrode for printable OSCs. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: POLYMER SOLAR-CELLS; OXIDE ANODE; NANOPARTICLE; PERFORMANCE